Tailed Lytic Bacteriophages of Soft Rot Pectobacteriaceae - Konstantin A. Miroshnikov; Peter V. Evseev; Anna A. Lukianova; Alexander N. Ignatov (Microorganisms, 2021)
The study of the ecological and evolutionary traits of Soft Rot Pectobacteriaceae (SRP) comprising genera Pectobacterium and Dickeya often involves bacterial viruses (bacteriophages). Bacteriophages are considered to be a prospective tool for the ecologically safe and highly specific protection of plants and harvests from bacterial diseases. Information concerning bacteriophages has been growing rapidly in recent years, and this has included new genomics-based principles of taxonomic distribution. In this review, we summarise the data on phages infecting Pectobacterium and Dickeya that are available in publications and genomic databases. The analysis highlights not only major genomic properties that assign phages to taxonomic families and genera, but also the features that make them potentially suitable for phage control applications. Specifically, there is a discussion of the molecular mechanisms of receptor recognition by the phages and problems concerning the evolution of phage-resistant mutants.